El efecto de la inflación en el crecimiento de las inversiones: una nota - De Faro, Clovis (El Colegio de México, A.C., 1998)
Motivated by the pioneering work of Brenner and Venetia (1983), henceforth designated as BV, a previous note that focused attention on the effect of taxation on the optimal duration of investments in a non-inflationary environment (de Faro, 1996), the present note is aimed at investigating the effects of inflation on the optimal duration of investments. Specifically, considering the no-reinvestment case only, our objective is to include in the analysis both a numerical illustration of the peculiar results of BV as well as indexation procedures that have been used in some high inflation economies.